Estudio del sistema de agua potable para la lotización Santa Isabel cantón La Troncal provincia del Cañar - Calle Aulestia, Freddy Giovanny (2013)
This research was conducted in order to find the optimal way to provide potable water service to Santa Isabel Allotment because it is a right of every living being and thus comply with the rules of good living . The research work is to design an optimal manner a system of potable water supply to the inhabitants of the lotizacion and these are developed in chapters. The design is performed by the initial calculation to know the consumption of drinking water that will need the lotizacion considering the technical standards for these calculations , using the polygon method determining our areas of contribution and Manning 's formula and Hazen-Williams was employed….